A lineage-specific Exo70 is required for receptor kinase-mediated immunity in barley - Holden, Samuel; Bergum, Molly; Green, Phon; Bettgenhaeuser, Jan; Hernández-Pinzón, Inmaculada; Thind, Anupriya; Clare, Shaun; Russell, James M; Hubbard, Amelia; Taylor, Jodi; Smoker, Matthew; Gardiner, Matthew; et al. (Science advances, 2022)
In the evolution of land plants, the plant immune system has experienced expansion in immune receptor and signaling pathways. Lineage-specific expansions have been observed in diverse gene families that are potentially involved in immunity but lack causal association. Here, we show that Rps8-mediated resistance in barley to the pathogen Puccinia striiformis f. sp. tritici (wheat stripe rust) is conferred by a genetic module: Pur1 and Exo70FX12, which are together necessary and sufficient. Pur1 encodes a leucine-rich repeat receptor kinase and is the ortholog of rice Xa21, and Exo70FX12 belongs to the Poales-specific Exo70FX clade. The Exo70FX clade emerged after the divergence of the Bromeliaceae and Poaceae and comprises from 2 to 75 members in sequenced grasses. These results demonstrate the requirement of a lineage-specific Exo70FX12 in Pur1-mediated immunity and suggest that the Exo70FX clade may have evolved a specialized role in receptor kinase signaling.